THE PORTRAIT OF POLITICAL DISCRIMINATION AGAINST BLACK PEOPLE IN AMERICA IN 1960S AS REFLECTED IN THE NOVEL GO SET A WATCHMAN BY HARPER LEE - Anggita Nindya Sari; Siti Hafsah; Wahyuni Wahyuni (Prologue: Journal on Language and Literature, 2019)
There are objectives that become the purpose of this research: 1) to describe the factors cause the political discrimination against black people in America in 1960s as reflected in the novel Go Set A Watchman by Harper Lee and 2) to find the strategy of political discrimination against black people in America in 1960s portray in the novel Go Set A Watchman by Harper Lee. The theory used in this research is the Sociology of Literature and hegemony theory by Gramsci about dominance and direction/leadership and discrimination as supporting theory. The methodology employed is qualitative research which the researcher aims to study the the issue of political discrimination and the factors cause the political discrimination. In the process of collecting data, the researcher collected from primary and secondary data. The primary data is the story and relation issue in the novel which about the factors causing political discrimination and the strategy of political discrimination against black people in America in 1960s. The researcher concludes that the issue reflected in the novel, there are some factors causing the political discrimination against black people, they are dominance and direction/leadership which is the phase of hegemony. The strategy of political discrimination against black people are discrimination in accepting the equality as the opportunity in part of government agency, discrimination in sharing the responsibility of citizenship and discrimination of the rights to vote. Those discrimination has the purpose to limiting black people become the participant of board council.